Is the sleep structure vulnerable to indoor air contaminants? - Belo, Joana (2019)
What do we know? Sleep has a vital role in human welfare; low ventilation rates; breathing zone closer to potential sources of pollutants; lack of studies about indoor exposure during sleep. The present study aimed to assess IAQ during sleep along with sleep quality in order to evaluate the associations between IAQ and sleep parameters.